Use of a combined method of photo-electrocoagulation-oxidation for simultaneous removal of Ni, CN, Zn, and Cu from synthesized mine wastewater - Ahmad Shahedi; Ahmad Jamshidi-Zanjani; Ahmad Khodadadi Darban; Mehdi Homaee; Fariborz Taghipour (Results in Engineering)
A diverse range of heavy metals and toxic elements are present in the wastewater from mineral processing. A novel approach for eliminating contaminants from wastewater involves electrocoagulation (EC), which is occasionally employed in conjunction with additional techniques such as advanced oxidation to enhance the overall efficacy of pollutant removal. Therefore, in this study, for the simultaneous elimination of Ni, CN, Zn, and Cu, the combined method of EC-UV along with the oxidizing agents of hydrogen peroxide (HP) and ozone (O) were used. Based on the findings of this study, the utilization of integration of photo-electrocoagulation and oxidation methods together yielded the highest removal rates for Ni, CN, Zn, and Cu, with removal efficiencies reaching 100%, 98.8%, 95.2%, and 95.8%, respectively. The highest simultaneous elimination of the target pollutants was attained when stainless steel and iron were employed as anode electrodes, while aluminum and graphite served as cathodes. This optimal removal was achieved under conditions including the addition of 4 mg/L hydrogen peroxide, an ozone flow rate of 3 L/min, current density of 15 mA/cm², pH = 10, process duration of 10 min, and an electrode spacing of 5 cm in batch mode. The relatively high efficacy in removing pollutants was attributed to the simultaneous generation of hydroxyl radicals and superoxide, alongside the formation of coagulants produced through electrocoagulation. According to the promising results of this research, the integration of the advanced oxidation process with electrocoagulation demonstrates high efficacy in eliminating various contaminants, including both organic and inorganic pollutants, from wastewater.